Application of H∞ Filter on the Angular Rate Matching in the Transfer Alignment - Lijun Song; Zhongxing Duan; Jiwu Sun (Discrete Dynamics in Nature and Society)
The transfer alignment (TA) scheme is used for the initial alignment of Inertial Navigation System (INS) on dynamical base. The Kalman filter is often used in TA to improve the precision of TA. And the statistical characteristics of interference signal which is difficult to get must be known before the Kalman filter is used in the TA, because the interference signal is a random signal and there are some changes on the dynamic model of system. In this paper, the H∞ filter is adopted in the TA scheme of the angular rate matching when the various stages of disturbance in measurement are unknown. And it is compared with the Kalman filter in the same environment of simulation and evaluation. The result of simulation shows that the H∞ filter and the Kalman filter are both effective. The Kalman filter is more accurate than the H∞ filter when system noise and measurement noise are white noise, but the H∞ filter is more accurate and quicker than the Kalman filter when system noise and measurement noise are color noise. In the engineering practice, system noise and measurement noise are always color noise, so the H∞ filter is more suitable for engineering practice than the Kalman filter.